The Assessment of Bankruptcy Potential of Sharia Rural Banks in Indonesia - Amelia Pratiwi; Baiq Nurlita Dwi Puspita; Sony Wahyudi (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2019)
Abstract:This investigation is intended to assess the possibility of financial problems in Sharia Rural Banks (SBRs) in Indonesia. The financial ratio approach is chosen to measure the financial distress potential of SRBs which assesses the profitability, liquidity, efficiency and capital adequacy of 166 banks from 2013 to 2016. The model of panel estimation uses discriminant analysis is utilized in predicting financial distress in Indonesian SRBs. The outcomes of this research are, firstly, liquidity and efficiency are the most prominent variables in predicting financial difficulties in SRBs. The second is in further analysis of liquidity shows that most SRBs are very aggressive in disbursing credit to small and medium enterprises (SMEs), which are riskier than other economic sectors. In addition, a deeper analysis of bank efficiency indicates that the highest expense component of SRBs' other operating costs is employee and administration costs. Keywords: financial distress, financial ratios, Sharia rural banks, discriminant analysisPengujian Potensi Kebangkrutan Grup Bank Pembiayaan Rakyat Syariah di IndonesiaAbstrakStudi ini bertujuan untuk menilai kemungkinan terjadinya masalah keuangan pada Bank Perkreditan Rakyat Syariah (BPRS) di Indonesia. Pendekatan rasio keuangan dilakukan untuk mengukur kemungkinan terjadinya financial distress yang menilai dari sisi profitabilitas, likuiditas, efisiensi dan kecukupan modal dari 166 bank selama 2013 hingga 2016. Model estimasi panel menggunakan analisis diskriminan diterapkan dalam memprediksi financial distress pada BPRS Indonesia. Hasilnya adalah, pertama, likuiditas dan efisiensi adalah variabel yang paling signifikan dalam memprediksi kesulitan keuangan di BPRS. Kedua, dalam analisis likuiditas lebih lanjut menunjukkan bahwa sebagian besar BPRS cukup agresif dalam mendistribusikan pembiayaan kepada usaha kecil dan menengah (UKM), yang lebih berisiko di bandingkan sektor ekonomi lainnya. Selain itu, analisis yang lebih dalam tentang efisiensi bank menunjukkan bahwa komponen biaya tertinggi dari biaya operasional lain BPRS secara rata-rata adalah biaya pegawai atau karyawan dan administrasi. Kata kunci: financial distress, rasio keuangan, BPRS, analisis diskriminan